Recent advances in self-lubricating metal matrix nanocomposites reinforced by carbonous materials: A review - Wenting Ye; Yeran Shi; Qing Zhou; Mingda Xie; Haifeng Wang; Benyebka Bou-Saïd; Weimin Liu (Nano Materials Science)
Metal matrix self-lubricating materials lie at the core of cutting-edge aerospace, mechanical, and electrical industries, which demand technological performances that cannot be met by traditional liquid lubricants. Rapid innovation in nanocarbon materials in recent years enabled rapid development of advanced nanocomposites for applications in structural engineering and functional devices. Carbonous materials (e.g., graphite, graphene and carbon nanotubes), exhibit a wide range of unique electrical, mechanical, and thermal properties, which are also considered ideal lubricating reinforcements for metal matrix nanocomposites (MMCs) with superior mechanical and tribological properties. In this review, we first showcase the distinctive features of the constituents commonly employed in self-lubricating MMCs, encompassing the high-strength metallic matrix and nano-carbonous reinforcement. Then, we present a comprehensive overview of the recent advancements in preparation techniques for these advanced MMCs, followed by an in-depth discussion on their corresponding tribological properties and wear mechanisms. We close this review by outlining key problems to be solved and the future trend of the development in self-lubricating MMCs.